Integrated Perspective of Scaffold Designing and Multiscale Mechanics in Cardiac Bioengineering. Issue 12 (4th October 2021) - Lou, Lihua; Lopez, Kazue Orikasa; Nautiyal, Pranjal; Agarwal, Arvind
Abstract : Although progress has been made, a fully functional and transplantable cardiac patch is elusive due to several challenges. These challenges emanate from a nonoptimal understanding of different fields and expertise in biomedical, material, tissue, medicine, chemistry, biology, and mechanical engineering. Therefore, herein, an integrated approach for scaffold design requirements is critically reviewed. The scaffold manufacturing methods and prospects of electrical and mechanical stimulation to promote the maturation and function of cardiac tissues are presented. The mechanical behavior of cardiac cells and tissue functions are a fundamental requirement for a functional patch. Methods, data analysis, and mathematic models for measuring and quantifying cellular and tissue mechanics are discussed. Overall, this article serves as an overview, indicating the need for an "integrated" and collaborative approach to designing and fabricating functional and implantable cardiac tissues. Abstract : This article serves as an overview, indicating the need to have an "integrated" and collaborative approach to designing and fabricating functional and implantable cardiac tissues. Scaffold manufacturing methods and prospects of electrical and mechanical stimulation to promote the function of cardiac tissues are presented. Methods, data analysis, and mathematic models for measuring and quantifying cellular and tissue mechanics are discussed.